Factors influencing microplastic contamination in bottled drinking water in Indonesia: a systematic review - Amir, Rahmi (BKM Public Health and Community Medicine, 2023)
Purpose: This study aimed to determine the content of microplastics in Indonesia, the factors that influence them, and their impact on the human body. Methods: This study uses a qualitative method with a systematic literature review approach by reviewing eight journals screened using the prism method according to the inclusion criteria with a database derived from Science Direct, PubMed, Google Scholar, and the Invivo application. Results: The results showed that the concentration of microplastics in bottled water was 7,043 - 8,339 particles/L with sizes ranging from small to large (10-5000 µm). The dominant form of microplastics was fibers and fragments, primarily white, with the dominant composition being polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET) polymers. Factors affecting microplastics in bottled drinking water include water sources, production processes, exposure to sunlight, and repeated use of bottles. Microplastics can cause hormonal imbalances, heart disease, infertility risk, digestive disorders, and growth inhibition. Ways to reduce MP particles in AMDK include traditional filtering of raw water, electrocoagulation, magnetic extraction, and membrane separation. Conclusion: This systematic literature review found that bottled drinking water in Indonesia contains 7,043 - 8,339 microplastic particles/L, primarily composed of PP, PE, and PET polymers. Factors influencing contamination include untreated waste disposal, high pollution levels, production processes, sunlight exposure, and repeated bottle use. These microplastics pose significant health risks, making it crucial to address these factors to reduce contamination and protect public health.